The Implementation of South Korea’s Military Technology Reform in The Perspective of Techno-nationalism - Resi Qurrata Aini; Febry Triantama (Sospol : Jurnal Sosial Politik, 2021)
Revolution in Military Affairs (RMA) requires fundamental reforms on its 3 main pillars, namely military technology, doctrine, and organizational reform. South Korea is one of the states that has taken steps to initiate the RMA through defense reform policies. South Korea have initiated its own version of RMA by prioritizing the revolution of military technology rather than any other aspects. This article aims to explain why South Korea prioritizes its military modernization through the development of its domestic defense industry. This research applies the concept of military techno-nationalism impulse with a qualitative approach and literature review method to collect data from official documents, websites of the government, journals, and scientific reports. The results of the research indicate that South Korea's choice to prioritize the development of its domestic defense industry is not merely pushed by the urgency to decrease its dependencies toward the United States, but also by the desire to pursue for strategic power to face the North Korean threat as well as other states around the region that full of antagonism atmosphere, to obtain broader economic benefits through the spin-off effect of industrialization, and to gain international prestige as one of the largest arms exporter as well as standing equal with other regional players.